A systematic overview of methods, their limitations, and their opportunities to investigate inattentional blindness. Issue 1 (9th October 2020) - Redlich, Dennis; Memmert, Daniel; Kreitz, Carina
Summary: During the past two decades, the interest in investigating the phenomenon of inattentional blindness strongly increased and resulted in a fraying of paradigms investigating this specific failure of awareness. We reviewed 129 full‐text articles containing 219 experiments for their design and methods to create awareness for the growing variety of inattentional blindness paradigms. Also, we promote a deliberate use of future paradigms (proposedly based on their functionality and representativeness) to improve the transferability of research findings to the real world. In general, we argue that paradigms should be well‐chosen based on the respective purpose, as the concept of inattentional blindness represents most likely several subtypes with different underlying mechanisms rather than a single phenomenon. Finally, we propose to include expectancy as a continuous variable into the definition of inattentional blindness rather than using it as an exclusion criterion.